تقدير القدرة الائتلافية و قوة الهجين لبعض الصفات الانتاجية المرتبطة بالغلة في هجن من القمح الطري - حربا, نزار; العك, وليد; الضحاك, ليلى (Latakia University Journal -Biological Sciences Series, 2016)
نفذت هذه الدراسة في مركز البحوث العلمية الزراعية بحماه خلال الموسمين الزراعيين 2013 و 2014 حيث تم في الموسم الأول التهجين بين ثمانية طرز وراثية من القمح الطري (Triticumaestivum) بطريقة التهجين نصف التبادلي .زرعت هجن الجيل الأولF1المتحصل عليها والتي بلغت(28) هجيناً في الموسم الثاني مع آبائها وفق تصميم القطاعات العشوائية الكاملة (RCBD) وبواقع ثلاثة مكررات لدراسة القدرة العامة والخاصة على التوافق وقوة الهجين للصفات المكونة للغلة الحبية (عدد السنابل / نبات – عدد الحبوب / سنبلة – وزن الألف حبة – الغلة الحبية ) .أظهرت النتائج سيطرة الفعل المورثي التراكمي في صفتي عدد الحبوب / سنبلة ووزن الألف حبة في حين سيطر النمط المورثي اللاتراكمي على توريث صفات عدد السنابل /نبات والغلة الحبية للنبات .وتم تحديد عدد من الآباء (بحوث 4- دوما44828- أكساد1115- جولان2) التي تتمتع بقدرة عامة على التوافق.كما تم الحصول على العديد من الهجن ذات قدرة خاصة موجبة على التوافق ناتجة عن آباء ذات قدرة عامة ايجابية على التوافق وحاملة لقوة الهجين وأهم هذه الهجن:(جولان2×شام10)(أكساد1115×دوما4)(دوما2×أكساد1115) (دوما44828×جولان2) (دوما2×جولان2).وتم الحصول على هجن حاملة لقوة الهجين بالنسبة للأب الأعلى : (دوما44828×جولان2) (بحوث6×دوما4) (دوما44828×شام10) (دوما2×أكساد1115)للصفات عدد السنابل/نبات – عدد الحبوب/سنبلة – وزن 1000حبة – الغلة حبية/نبات على التوالي .This study was carried out through the cooperation between the Faculty of Agriculture Tishreen University and the General Commission of Agricultural Scientific Researches in Hama during 2013 and 2014 successive seasons.Eight soft wheat(Triticumaestivum)genotypes were crossed using half diallel method .The(28) crosses were grown along with their parents in randomized complete block with three replications to estimate general combiningability , specific combining ability, and both mid and high parent heterosis for number of spikes /plant , number of grains /spike , thousand grain weight and grain yield.The results indicated that both additive and non- additive types of gene action were important in the inheritance of traits under study with preponderance of additive gene effects for number of grains /spike and thousand grain weight,Non – additive gene effects were pronounced in the inheritance of number of spikes /plant and grain yield.High general combiners for thesecharacters were obtained and the most important parents were: Bohouth 4- Douma 44828-Acsad1115- Golan2.Many positive specific combiners having both mid and high parent heterosis and derived from positive general combiners were obtained such as(Golan2×Cham10) – (Acsad1115×Douma4)(Douma44828×Golan2) and (Douma 2×Golan2).Results also indicated that some hybrids: (Douma44828×Golan2) (Bohouth6×Douma4) (Douma44828×Cham10) (Douma2×Acsad1115) had heterosis compared to higher parent for number of spikes /plant , number of grains / spike , Thousand grain weight and grain yield..